Vertebrobasilar Dolichoectasia as a Cause of Trigeminal Neuralgia. A Case Report - Ada Sánchez Lozano; Didiesdle Herrera Alonso; Ricardo Verdecia Fraga (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Vertebrobasilar dolichoectasia as a cause of trigeminal neuralgia is a condition whose true incidence is still unknown. These cases have been estimated between 2 to 6% of them all. Clinical manifestations can be diverse and include stroke, cognitive symptoms and facial hemispasm. We present the case of a 68 years old male patient with white skin and a history of hypertension and trigeminal neuralgia ailment that attained second and third branches for about 10 years of evolution and refractory to medical treatment. In the studies performed, vertebrobasilar dolichoectasia was diagnosed as the cause of pain.